DEVELOPMENT AND VALIDATION OF AN UPDATED SYSTEM FOR DOWN-HOLE SEISMIC TESTING TOGETHER WITH PIEZOCONE - Braus, Guilherme Bravo [UNESP]; Gimenez Junior, Sergio Antônio [UNESP]; Rocha, Breno Padovezi [UNESP]; Giacheti, Heraldo Luiz [UNESP] (Sociedade Brasileira de Geofisica, 2025)
This paper presents the updated version of a system that uses a probe and software to carry out down-hole seismic testing in conjunction with piezocone to determine shear wave (Vs) and compressional wave (VP) velocities for geotechnical site characterization. The system was used in down-hole tests carried out at experimental research sites located in the interior of the state of São Paulo, Brazil, where reference Vs and VP values determined by cross-hole and down-hole tests are available. The updated seismic probe has six geophones: three for S wave recordings spaced 0.5 m apart and three for P wave recordings, also spaced 0.5 m apart. The updated software integrates data acquisition, allows the visualization of S and P wave traces and calculates Vs using the true interval method. The VP profiles could only be determined by the pseudo-time interval using commercial software. The developed system is considered efficient for determining Vs profiles in the way it was used. Further studies are needed to better understand the propagation of P waves, as well as to improve the system and the method for determining VP profiles.
Keywords: geophysical site characterization; hybrid tests; P waves; S waves; seismic probe